Caregivers’ burden and schizophrenia patients’ quality of life: Sequential mediating effects of expressed emotion and perceived expressed emotion - Wei, Yicheng; Peng, Yanan; Li, Yan; Song, Lanjun; Ju, Kang; Xi, Juzhe (Frontiers in Psychiatry, 2022)
Background: Increasing attention has been paid to the role of caregivers’ burden in affecting quality of life (QoL) of schizophrenic patients. However, less is known about potential mediation mechanisms underlying this relationship. The current study aimed to explore the sequential mediating effect of expressed emotion and perceived expressed emotion on the relationship between care burden and quality of life among people with schizophrenia. Methods: 135 Chinese families (one patient and one caregiver) participated in this study. Caregivers reported their care burden and expressed emotion, patients reported their perceived expressed emotion and quality of life. Results: The results of the correlation analysis showed that care burden was negatively related to patients’ quality of life, including physical, psychological, and social relationships domains, with patients’ sex, age, educational level, employment status, and medication-taking as covariates. The sequential mediating effects of criticism and perceived criticism between care burden and quality of life were not significant. However, the sequential mediating effects of emotional over-involvement and perceived emotional over-involvement between care burden and quality of life (including physical and psychological domain) were significant. Conclusions: The results indicated that reducing the burden and expressed emotion of caregivers could be helpful to improve schizophrenia patients’ quality of life.